Implementation of Religious Moderation Values at SMAN 6 Kediri - Fahrul Rozi; Syafik Ubaidila (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the implementation of religious moderation values at SMAN 6 Kediri and their impact on the development of students’ character. The background of this research lies in the school’s religious and cultural diversity, which requires an educational strategy based on tolerance, justice, and balance (wasathiyah) to prevent intolerance and radicalism. The research employed a descriptive qualitative approach with a case study design. Data were obtained through observations, in-depth interviews with teachers and students, and document analysis of school policies and learning activities. Data analysis was conducted thematically using triangulation techniques to ensure the validity of the findings. The results show that the values of religious moderation are integrated through contextual learning methods, participatory discussions, cross-subject collaboration, and curriculum support. This implementation has enhanced students’ understanding of the importance of harmony in diversity, shaped inclusive and tolerant character traits, and strengthened a harmonious school climate. The main challenge lies in differences in background and individual character, which influence the level of acceptance of these values. Overall, this study confirms that the application of religious moderation significantly contributes to character building and fostering harmony in the school environment.